Analisis Undur Intrinsik Pada Cerpen “SENYUM KARYAMIN” Karya Ahmad Tohari - Yorensina Anip Kalakmabin; Jelwita Waruwu (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
This study analyzes the intrinsic elements in the short story "Senyum karyamin" by Ahmad Tohari. This analysis aims to reveal the depth of meaning contained in the short story "Senyum Karyamin" through the study of its intrinsic elements. By focusing on themes, characterization, plot, setting, viewpoints, language style, and mandate, this research seeks to understand how Ahmad Tohari manages to present a portrait of a simple but meaningful life through the character of Karyamin. This research uses a descriptive analytical method to explain how the intrinsic elements in the short story "Senyum Karyamin" by Ahmad TohariThis research uses an objective approach, which is an approach that specializes in the literary work in a structured, systematic manner. The research method used in analyzing the short story "Senyum Karyamin" by Ahmad Tohari is using a qualitative descriptive research method which is to analyze thoroughly, broadly, and in-depth. In this study, the author analyzes the intrinsic elements of the short story "Senyum Karyamin" by Ahmad Tohari which has results, namely themes, characters, characterization, plot, point of view, setting, language style, and mandate. The benefits of this research can help to understand the content and message conveyed by the author to the reader. By using easy-to-understand words, a very touching story conflict, this short story allows me to better understand what the short story is about.